Penanganan Sistem Drainase Parit M. Sohor Di Kota Pontianak - Doddy Cahyadi Saputra; Fairuz Adibah; Hervian Handika Sugasta; Dimas Puji Santosa; Boy Rangga (Universitas Teuku Umar, 2025)
High intensity rainfall that occurs can cause puddles if the condition of the drainage system is not well maintained. The development of Pontianak City Infrastructure has resulted in land use changes that was originally in the form of vacant land converted into residential areas or other economic activities. The existing condition of the drainage channel at M. Sohor Road is not able to accommodate rainwater discharge in the rainy season. In the existing conditions for land use, there is no rainwater catchment area. The management of floods with arranging the drainage system has been ineffective so we need an environmentally drainage system arrangement concept. Identification of the hydrological and hydrolic conditions that exist in the catchment area of the M. Sohor channel is required. The hydrological analysis in this study includes testing the consistency of rainfall data in Pontianak City, selecting a rain distribution that matches the rainfall data pattern, calculating the time concentration, rainfall intensity and the total discharge from domestic discharge and design discharge of 2, 5, 10 years. The hydraulic analysis in this study includes the design of a channel cross section design as a channel normalization plan. The total flow discharge in M.Sohor channel for a 2-year return period is 2.22 m3/s, a 5-year return period of 2.75 m3/s and a 10-year return period of 3.09 m3/s. Environmental insight drainage can be done by planting shrub plants that can reduce air pollution such as Croton and Bougainvillea, arranging M. Sohor Road to be friendly with pedestrians controlling excess rainwater discharge caused by the rain process through rain water harvesting techniques.